Analisis Penerapan Manajemen di Puskesmas Pacet Berdasarkan PMK No. 44 Tahun 2016 Tentang Pedoman Manajemen Puskesmas - Muhammad Ulul Arham Al Hikami; Marianah Marianah; Setya Haksama (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
Puskesmas Pacet is a functional organization that functions as a center for community health development in Pacet. In order for the Puskesmas Pacet to be able to manage all work programs and health efforts properly and continuously, it is necessary to implement good management. For this reason, this study was made to analyze the suitability of the implementation of the management of Puskesmas Pacet with Puskesmas management guidelines in Permenkes No. 44 of 2016 concerning Guidelines for Management of Community Health Centers. This research is a descriptive study with a qualitative approach. The results of this study indicate that the management of Puskesmas Pacet is in accordance with the Permenkes No. 44 of 2016 concerning Puskesmas management guidelines although there are some shortcomings. Several technical obstacles were found, such as the lack of human resources which were not immediately addressed by the Puskesmas. In the future, Puskesmas Pacet is expected to immediately propose HR recruitment and improve performance evaluation so that activities can run more optimally and the performance of Puskesmas Pacet will be better.